Computer-Aided Drug Repurposing: A Cyclooxygenase-2 Inhibitor Celecoxib as a Ligand for Estrogen Receptor Alpha - Enade Perdana Istyastono; Florentinus Dika Octa Riswanto; Sri Hartati Yuliani (Universitas Gadjah Mada, 2015)
A cyclooxygenase-2 (COX-2) inhibitor celecoxib has been previously reported to have cytotoxic activities towards gastric, prostate, ovarian, colon and breast cancer cell lines. This article reports that the cytotoxic activities of celecoxib could be resulted from its activity as a potent ligand for estrogen receptor alpha (ERα). Aided by molecular docking simulations, an in silico test to examine whether celecoxib is a ligand for estrogen receptor alpha (ERα) was performed followed by in vitro test employing cytotoxic assay using 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) method. The compound was extracted from Celebrex®. Measured by using UV spectrophotometric method at 255.5 nm, it was identified that the content of celecoxib was 102.15 mg/271.48 mg capsule content. The in silico test indicated that celecoxib is a potent ligand for ERα. This finding was confirmed experimentally by an in vitro test that celecoxib has a comparable activity as an ERα ligand to tamoxifen, a drug of choice for breast cancer treatment.